The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/en14102810
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Correction of the Spatial Orientation Angles of the Unmanned Aerial Vehicle Using Real Time GNSS, a Shoreline Image and an Electronic Navigational Chart

Abstract: Undoubtedly, Low-Altitude Unmanned Aerial Vehicles (UAVs) are becoming more common in marine applications. Equipped with a Global Navigation Satellite System (GNSS) Real-Time Kinematic (RTK) receiver for highly accurate positioning, they perform camera and Light Detection and Ranging (LiDAR) measurements. Unfortunately, these measurements may still be subject to large errors-mainly due to the inaccuracy of measurement of the optical axis of the camera or LiDAR sensor. Usually, UAVs use a small and light Inerti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Dynamic information such as navigation marks and the water level are displayed on the map in real time with good precision. It is suggested that new technologies, such as uncrewed aerial vehicles and ships ( 30 , 31 ), should be combined to improve the renewal speed of I-ENC.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic information such as navigation marks and the water level are displayed on the map in real time with good precision. It is suggested that new technologies, such as uncrewed aerial vehicles and ships ( 30 , 31 ), should be combined to improve the renewal speed of I-ENC.…”
Section: Discussionmentioning
confidence: 99%
“…The use of camera images, e.g., mounted on unmanned aerial vehicles (UAV), is particularly interesting. For example, the authors of [27] proposed a method to correct spatial orientation angle based on a shoreline image for use in coastal and port environments. The use of this type of tool, such as passive cameras, develops the interdisciplinary aspect of navigation, reaching to the achievements of image processing, signal processing and robotics.…”
Section: Related Workmentioning
confidence: 99%
“…Due to their extensive capabilities, GNSS/INS systems are primarily used in navigation and transport applications. These include tests using Unmanned Aerial Vehicles (UAV) [8][9][10] and Unmanned Surface Vehicles (USV) [11,12], locating mobile phones [13], indoor [14], terrestrial [15] and space [16] navigation, geodetic [17][18][19] and hydrographic surveys [20][21][22], operating Autonomous Ground Vehicles (AGV) [23][24][25], rail transport, in particular for the purposes of High-Speed Rail (HSR) [26,27], road transport [28][29][30] or preventing intentional interference [31,32].…”
Section: Hydrographic Surveys Are Among the Navigation Applications That Commonly Use Global Navigation Satellite Systems (Gnss) Accordinmentioning
confidence: 99%